Timing of death from tumor recurrence after curative gastrectomy for gastric cancer - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2004)
In Western literature, there are few studies investigating the predictors of early versus late recurrence after curative gastrectomy for gastric cancer. The current study analyzed (1) patients who died of recurrent gastric cancer and (2) prognostic factors, which can be applied to timing of death from tumor recurrence. Of 492 patients who underwent curative resection (R0) for gastric cancer in the Department of Surgery, Medical Faculty of Istanbul between 1994 and 2000, 142 patients who died of recurrence were included into study. None of the patients had received postoperative adjuvant treatment. The patients were divided into 2 groups: an early recurrence group that included 102 patients who recurred and died within 2 years after surgery, and a late recurrence group, which included 40 patients who died of recurrence more than 2 years after surgery. Clinicopathologic findings were compared between the early and late recurrence groups. Multivariate analysis was performed to investigate the independent factors, which are predictive for early versus late recurrence, and prognostic factors independently associated with the survival period. In multivariate analysis, the early recurrence group, when compared with the late recurrence group, was characterized by lymph node metastasis (N1-3 versus NO; P = 0.002). Overall survival was influenced by nodal status (N1-3 versus NO; P = 0.003), type of operation performed (radical total versus radical subtotal gastrectomy; P = 0.003), Eastern Cooperative Oncology Group performance status (PS 3-4 versus PS 1-2; P = 0.004), and tumor localization (cardia versus corpus and antrum; P = 0.046). In contrast, T stage of the disease was not prognostic for survival, although it was close to statistical significance (P = 0.066). Multivariate analysis showed that poorer performance status at initial presentation (P = 0.001) and lymph node metastasis (P = 0.032) independently correlated with overall survival (P = 0.002). Lymph node status was the most important factor predictive for early versus late recurrence and patients with lymph node metastases were at more risk of death within 2 years after curative operation for gastric cancer. Postoperative chemoradiotherapy should be especially recommended for patients at high risk of recurrence of adenocarcinoma of the stomach or who have undergone curative resection.
Keywords: tumor recurrence; gastric cancer; lymph node status; SUBTOTAL GASTRECTOMY; SURGICAL-TREATMENT; C-ERBB-2 PROTEIN; ADENOCARCINOMA; CARCINOMA; SURVIVAL; STOMACH; OVEREXPRESSION; SPLENECTOMY; PROGNOSIS